DISCOURSE ON CORRUPTION COUNTERACTION IN NETWORK TRADE - L. A. Zhigun; E. M. Feoktistova (Russian Journal of Economics and Law)
Objective: to determine the specific forms of corruption and promising methods to counteract corruption in network trade.Methods: the combination of inductive observations, comparisons, generalizations, facts and trends of corruption in network trade with a logical analytical deduction of economic theories and the corruption concept are the basis of the study and provide an opportunity, on the one hand, to assess the level of compliance of theoretical concepts of corruption with the practice and, on the other hand, to determine their applicability to organize opposition and create conditions to prevent its occurrence; to summarize the features of corruption in the form of a kickback, the discourse method was applied in this work.Results: on the basis of theoretical provisions and facts of corruption in trade, it is proved that it has typical characteristics of corruption in commercial and non-profit organizations. The key reasons are identified why corruption occurs in trade. Among them, supply of poor quality goods at inflated prices, leading to bribery in the form of «personal bonus» to administrator of the trading organization when selling goods by57Диалектика противодействия коррупцииThe dialectics of anti-corruptionАктуальные проблемы экономики и права. 2015. № 4Actual Problems of Economics and Law. 2015. No. 4an unscrupulous supplier, and also supply goods to the trade organizations, which will not buy without kickback. Most of these corrupt deals are carried out by natural monopolies in the form of state and municipal procurement. In some cases, the kickback is the argument, stimulating the decision to introduce new and advanced technologies. The factors that lead to corruption in trade are listed, and reasonable methods to counteract it are grounded, allowing to create conditions for its eradication in other branches of business as well.Scientific novelty: for the first time a generalization has been made about the deficit as the driving force in the mechanism, when the bribe- givers and bribe-takers change places.Practical significance: the main provisions and conclusions of the article can be used in the research of specific forms of corruption and in the developing methods of combating corruption both in trade and in other business areas.